Digital financial transformation in religious traditions: Analyzing Qris usage intentions for dana Punia in Bali - Rahmayanti, Putu Laksmita Dewi; Giantari, I Gusti Ayu Ketut; Ekawati, Ni Wayan; Setiawan, Putu Yudi (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the influence of usage barriers, risk barriers, tradition barriers, product knowledge, attitude, and personal norms on the intention to use QRIS (Quick Response Code Indonesian Standard) for almsgiving at temples in Bali. This research provides culturally grounded recommendations for temple managers, QRIS service providers, and policymakers to promote QRIS adoption in religious settings. A quantitative survey method was employed, involving 189 temple devotees in Bali. Structural Equation Modeling (SEM) was used to analyze the relationships among variables, including the effects of attitude and personal norms as mediators. The results reveal that usage and tradition barriers significantly and negatively affect the intention to use QRIS, while risk barriers show a minor negative impact. Conversely, product knowledge, attitude, and personal norms positively and significantly influence QRIS adoption. Attitude and personal norms also serve as key mediators. The findings highlight the importance of reducing technological and cultural barriers and enhancing digital literacy. Practical implications include the need for consistent user education, involvement of religious leaders, and the development of trust through transparent practices and better user experiences. This study contributes original insights into the intersection of technology adoption and religious-cultural practices, offering a roadmap for sustainable QRIS integration in similar contexts.